Quantum Speedup for the Fast Fourier Transform? - Monroe, Don (Communications of the ACM, 2023)
The article focuses on the work of Peter Shor, professor of applied mathematics at Massachusetts Institute of Technology (MIT), on how quantum computers could break current public-key encryption schemes. The author explains how this method utilizes the the quantum implementation of a Fourier transform.